1992
DOI: 10.1093/aje/136.7.819
|View full text |Cite
|
Sign up to set email alerts
|

Does Recent Alcohol Consumption Reduce the Risk of Acute Myocardial Infarction and Coronary Death in Regular Drinkers?

Abstract: This study, conducted in Auckland, New Zealand, over 2 years from March 1986, used a case-control design to investigate the hypothesis that alcohol acutely increases the risk of both nonfatal myocardial infarction and coronary death in the 24 hours after drinking, among regular drinkers. The nonfatal myocardial infarction analyses included 278 male and 60 female cases identified from a population-based coronary heart disease surveillance program and 458 male and 266 female controls randomly selected from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…Using cases as their own matching controls equalizes past alcohol intake. For example, the traditional case-control study by Jackson et al (15) yielded an odds ratio among men of 0.75 (0.62 to 0.90) for alcohol intake during the 24 h before onset of nonfatal MI, compared with a comparable 24-h period in matched controls. This is consistent with the well-established inverse association between alcohol intake and MI, which could be caused by a combination of ethanol effects-a chronic cumulative protective effect plus a repeated transient protective effect.…”
Section: Transience Of Effectmentioning
confidence: 99%
“…Using cases as their own matching controls equalizes past alcohol intake. For example, the traditional case-control study by Jackson et al (15) yielded an odds ratio among men of 0.75 (0.62 to 0.90) for alcohol intake during the 24 h before onset of nonfatal MI, compared with a comparable 24-h period in matched controls. This is consistent with the well-established inverse association between alcohol intake and MI, which could be caused by a combination of ethanol effects-a chronic cumulative protective effect plus a repeated transient protective effect.…”
Section: Transience Of Effectmentioning
confidence: 99%
“…59,73 The cardiovascular benefits of alcohol consumption for women appear to be associated with both habitual and recent alcohol consumption. 74 Mechanisms by which low-level alcohol consumption decreases the risk of cardiovascular disease most likely include chronic alterations in lipids and lipoproteins, as well as more acute antithrombotic effects. 67,[75][76][77] Studies have consistently demonstrated a positive association between alcohol intake and levels of the cardioprotective high-density lipoproteins (HDLs) in women.…”
Section: Medical Risks Of Drinking For Women Compared With Menmentioning
confidence: 99%
“…Forty grams and 20 g alcohol/day for men and women, respectively, are at the upper end of the moderation range. [21][22][23][24] Subsequent studies have also independently assessed the association between alcohol consumption and cognitive function and have affirmed the observations of Zuccala and colleagues 26 but have also provided more detailed data. [158][159][160][161][162] For example, Reid and colleagues 161 in a study of 760 US men aged 65 years or older showed that current light to moderate alcohol consumption which was considered as up to approximately 70 g/week, compared to abstinence, had better cognitive function.…”
Section: Effect Of Wine On Cognitive Functionmentioning
confidence: 71%
“…Latruffe and colleagues 85 examined the effect of resveratrol on two different human tumor cell lines, and has shown that resveratrol is actually taken up by the cells, whereupon it is conjugated and released into the cell medium by the hepatic HepG2 cells and to a lesser extent by colorectal tumor SW480 cells. 21 Phenolic compounds may not be antiproliferative or active against all tumor cell lines, however, as no uptake and conjugation was observed with cells from the intestine. Elattar and Virji 78 examined the effect of quercetin alone and in combination with resveratrol on human oral squamous carcinoma cells (SCC-25), and showed that quercetin is an equipotent inhibitor of SCC-25 cell growth and DNA synthesis, but the combination of quercetin and resveratrol was most potent.…”
Section: Potential Mechanism Of Action: Role Of Wine-derived Phenolicmentioning
confidence: 99%
See 1 more Smart Citation